Can red yeast rice and olive extract improve lipid profile and cardiovascular risk in metabolic syndrome?: a double blind, placebo controlled randomized trial - Verhoeven, Veronique (BMC Complement Altern Med, 2015)
BACKGROUND: Metabolic syndrome (MetS) comprises a spectrum of clinical phenotypes in which dyslipidemia, dysglycemia and hypertension are clustered and where all share a high level of oxidative stress and an increased risk of cardiovascular disease. This study examines the effect of a nutritional supplement combining red yeast rice and olive fruit extract on the lipid profile and on oxidative stress in a population of patients with MetS. METHODS: In a double blind placebo controlled randomized trial, 50 persons with MetS, as defined by the ATPIII criteria, received the study product or placebo for 8 weeks. The study product contained 10.82 mg of monacolins and 9,32 mg of hydroxytyrosol per capsule, and is commercialized as Cholesfytol plus. The primary outcome measure was the difference in LDL reduction between intervention and control groups. Furthermore, differences in changes of CH, HDL, ApoA1, ApoB, HbA1c and oxLDL were measured, as well as side-effects, CK elevation, changes in clinical parameters and in cardiovascular risk. RESULTS: In the intervention group, LDL cholesterol was lowered by 24% whereas it increased by 1% in the control group (p < 0.001). Other effects observed were a change in total cholesterol (−17% in the intervention group vs +2% in the control group, p < 0.001), apolipoprotein B (−15% vs +6%, p < 0.001), and TG (−9% vs + 16%, p = 0.02). Oxidized LDL decreased by 20% vs an increase of 5% in the control group (p < 0.001). Systolic and diastolic arterial blood pressure decreased significantly by 10 mmHg (vs 0% in the control group, p = 0.001) and 7 mmHg (vs 0% in the control group, p = 0.05) respectively. One person in the intervention group, who suffered from Segawa’s syndrome, dropped out because of severe muscle ache. CONCLUSIONS: The combination of active products in this study may be an alternative approach to statins in people who do not need, or cannot or do not want to be treated with chemical statins. Side effects, effects on oxidative stress and on glucose metabolism need to be examined more thoroughly. TRIAL REGISTRATION: Clinicaltrials.gov NCT02065180 (February 2014).